Adaptability in Moth Bean (Vigna Aconitifolia (Jacq.) Marechal) for Seed Yield in Rainfed Conditions - Jindal, S K; Vir, Satya (Annals of Arid Zone, 2016)
Twenty two genotypes of moth bean (Vigna aconitifolia (Jacq.) Marechal) were evaluated for their seed yield over five environments to gather information on stability parameters. Both linear and non-linear components of g X e interactions were significant and the prediction of performance across environments appeared to be difficult. The genotypes namely IPCMO 911 and IPCMO 259 were high yielding and phenotypically stable across rainfed environments.